Quantitative prediction of therapeutic antibody pharmacokinetics after intravenous and subcutaneous injection in human - Haraya, Kenta; Tachibana, Tatsuhiko; Nezu, Junichi (Drug metabolism and pharmacokinetics, 2017)
Prediction of the plasma/serum mAb concentration–time profile in human is important to determine the required dose regime. This study proposes an approach for predicting the plasma/serum mAb concentration–time profile after intravenous and subcutaneous injection in human based on comprehensive analysis of reported pharmacokinetic data. Optimal scaling exponents from cynomolgus monkey to human for CL, Q, Vc, and Vp were estimated as 0.8, 0.75, 1.0, and 0.95, respectively. The estimated exponents were used to predict plasma/serum mAb concentration–time profile in human from pharmacokinetic data in cynomolgus monkey, and the results had reasonable accuracy with symmetric variability of prediction. Then, data reported for pharmacokinetics in human were used to estimate optimal ka and F after subcutaneous injection. The geometric mean of ka was suitable to predict Tmax, and F which was estimated from CL was suitable to predict Cmax. Our approach is useful for predicting the plasma/serum mAb concentration–time profile after intravenous and subcutaneous injection in human. Moreover, the study also investigated the possibility of predicting pharmacokinetic parameters of mAbs with increased FcRn binding mutations in human and found that our approach of prediction based on reported pharmacokinetic data may also be applicable to mAbs with these mutations. [Display omitted]